Text and Practice in Teaching Translation: Documenting the Process - Julia Eka Rini (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
Documenting the process of translation has several advantages for both teachers and students in a translation class in an English, or any language, department. It is not only useful for preventing the students from using translation applications in doing the assignments, but also useful for teaching them to evaluate and to revise their translation. Besides making students accustomed to expressing their thoughts in writing, process-oriented teaching inspires them to think in detail and inspires lecturers to conduct process-oriented translation research.